The Influence of Competence and Organizational Culture on Employee Performance at PT PLN (Persero) Maluku and Papua Development Main Unit - Siahaan, Mario Iriando; Sibarani, Mentiana (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study investigates the influence of competence and organizational culture on employee performance at PT PLN (Persero) Unit Induk Pembangunan Maluku dan Papua. Adopting a quantitative research design, data were collected from 71 employees using a structured questionnaire, selected through proportionate stratified random sampling. The analysis was conducted using multiple linear regression with the help of SPSS software. The results reveal that both competence and organizational culture significantly influence employee performance, both partially and simultaneously. Competence, as reflected in employees’ knowledge, skills, and attitudes, positively impacts performance by enhancing work quality and individual contribution. Meanwhile, organizational culture, characterized by shared norms, values, and beliefs, fosters a cohesive and productive work environment that supports improved employee performance. The study concludes that improving employee competence and cultivating a supportive organizational culture are key to optimizing employee output and organizational success. These findings provide valuable insights for human resource development strategies within state-owned infrastructure enterprises.